Implementasi Strategi Pembelajaran pada Pembelajaran Bahasa Indonesia Kelas 3 SDN Cipondoh 3 Kota Tangerang - Magdalena, Ina; Wulandari, Sri; Julianis, Tania (YASIN, 2023)
Indonesian is the language that our society uses to communicate, interact with other people. One of the important subjects taught is Indonesian at school. The problem with this research is that teachers use conventional learning techniques. The reason is that learning is not varied or interesting, it is still teacher-centered, and students still have difficulty understanding the concept of learning materials. Implementation of Indonesian language learning aims to find out strategies for learning Indonesian at SDN Cipondoh 3 Tangerang city. The research methodology which is a case study research takes a qualitative approach . This lesson was conducted in class 3 at SDN Cipondoh 3 Tangerang City. From the findings of this study it shoes that learning Indonesian in class 3 at SDN Cipondoh 3 Tangerang city is not optimal.